Parkinsonism and prolonged cognitive decline as a manifestation of cryptococcal meningitis in a renal transplant patient. Issue 1 (19th January 2022) - Nelles, Ricky; Britton, Sumudu; John, George Tharayil; Denaro, Charles
Abstract : We report a case of a 67-year-old male recipient of a second renal allograft, presenting with a 9-month history of progressive cognitive and physical decline with features of Parkinsonism. He was HIV-negative. Serum and cerebrospinal fluid (CSF) cryptococcal antigen was positive though CSF culture was sterile. He had progressive deterioration despite induction and consolidation antifungal treatment. Postmortem brain examination confirmed a large burden of yeast forms in the substantia nigra with widespread chronic meningitis. The significant delay in presentation and diagnosis owing to the atypical, subacute neurocognitive features serves as a timely reminder of the variety of neurological presentations that may be associated with cryptococcal infection in solid organ transplant recipients.